1992
DOI: 10.1021/j100205a086
|View full text |Cite
|
Sign up to set email alerts
|

Redox reactions for Group 5 elements, including element 105, in aqueous solutions

Abstract: Standard redox potentials Eo(Mz++X/MZ+) in acidic solutions for group 5 elements including element 105 (Ha) and the actinide, Pa, have been estimated on the basis of the ionization potentials calculated via the multiconfiguration Dirac-Fock method. Stability of the pentavalent state was shown to increase along the group from V to Ha, while that of the tetra-and trivalent states decreases in this direction. Our estimates have shown no extra stability of the trivalent state of hahnium. Element 105 should form mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 7 publications
2
40
0
3
Order By: Relevance
“…This analysis also gave the changes in the enthalpies and Gibbs free energies due to relativistic contributions in the MCSCF computations. Similar calculations were performed also for Db [138]. The stability of the pentavalent state was shown to increase along the group from vanadium to tantalum, while that of the tetra-and trivalent states decreases with increasing nuclear charge.…”
Section: Early Mcscf Calculations Of Superheavy Elements: Ionization mentioning
confidence: 62%
“…This analysis also gave the changes in the enthalpies and Gibbs free energies due to relativistic contributions in the MCSCF computations. Similar calculations were performed also for Db [138]. The stability of the pentavalent state was shown to increase along the group from vanadium to tantalum, while that of the tetra-and trivalent states decreases with increasing nuclear charge.…”
Section: Early Mcscf Calculations Of Superheavy Elements: Ionization mentioning
confidence: 62%
“…It was shown that the stability of the pentavalent state increases from V to Db, while the stability of the tetra-and trivalent state decreases. Although it was found that the stability of the maximum oxidation state decreases in going from Lr to Db, no extra stability of the trivalent state in Db was found [116]. It would be interesting to test this prediction in reduction experiments similar to the experiments performed on Lr [117].…”
Section: Theoretical Predictionsmentioning
confidence: 99%
“…Differences between the chemical behavior of Db and the extrapolated properties of an eka-tantalum could result from a larger ionic radius, a different effective charge, and a different radial extension of the 6d orbitals, which are most important in its molecular bondings [100,[110][111][112][113][114][115]. Redox potentials were estimated for the group 5 elements, including the pseudohomolog Pa, on the basis of ionization potentials from MCDF calculations [111,116]. It was shown that the stability of the pentavalent state increases from V to Db, while the stability of the tetra-and trivalent state decreases.…”
Section: Theoretical Predictionsmentioning
confidence: 99%
“…It was shown that the stability of the pentavalent state is increasing from V to Db, while the stability of the tetra-and trivalent state is decreasing. Although it was found that the stability of the maximum oxidation state decreases when going from element 103 to 105, no extra stability of the trivalent state in element 105 was found [121]. It would be interesting to test this prediction in reduction experiments similar to the experiments performed on element 103 [122].…”
Section: According To the Glückauf Equation Of Chromatography The Elmentioning
confidence: 99%
“…Differences in the chemical behavior of element 105 to extrapolated properties of an eka-tantalum could result from a larger ionic radius, a different effective charge, and a different radial extension of the 6d orbitals which are most important in its molecular bondings (Pershina et al [113][114][115], Fricke et al [112], Pershina et al [116][117][118][119][120]). Redox potentials were estimated for the group-5 elements including the pseudo-homolog Pa on the basis of ionization potentials from MCDF calculations [112,121]. It was shown that the stability of the pentavalent state is increasing from V to Db, while the stability of the tetra-and trivalent state is decreasing.…”
Section: According To the Glückauf Equation Of Chromatography The Elmentioning
confidence: 99%